"How are we doing?", a tool for participatory monitoring and adaptive learning in multi-stakeholder fora - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The tool's generic version was tested in two management committees of protected areas in Peru, leading to a second version customized for these management committees and published by Peru's Service for Natural Protected Areas as an official government document to be implemented in 76 management committees (15% of Peru's territory).